Perancangan Alat Pencuci Ubi Jalar dengan Sistem Rotary - Bagus Yustia; Herru Santosa Budiono; Sigit Joko Purnomo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Sweet potatoes are an agricultural commodity widely consumed by the community and possess high economic value, particularly in the food processing industry. This study aims to design and analyze a rotary sweet potato washing machine using a static simulation approach to evaluate its structural performance and operational feasibility. The research methodology included design development, material selection, engineering calculations, and numerical simulation using static stress analysis. The calculation results showed that the washing drum has a volume of 141,442 cm³, with a diameter of 48 cm (radius = 24 cm) and a calculated height of 78.2 cm. These dimensions were determined to provide approximately 75% free space for sweet potato movement during the washing process. In addition, the required working water volume was calculated to be 70.7 liters, which is sufficient to ensure effective water circulation for dirt removal without causing overflow. Static simulation through stress testing produced a maximum stress value of 208.584 MPa and a minimum stress value of 0.005 MPa. The maximum displacement was 0.785 mm, while the minimum displacement was 0.000 mm. The calculated Factor of Safety (FOS) was 1.199, indicating that the frame structure is capable of safely withstanding the operational load. The results demonstrate that the proposed rotary washing machine design is structurally safe and suitable for sweet potato washing applications.